Log in to add a comment

## Answers

The Brainliest Answer!

**Solutions**

We first multiply all terms of the first equation by the LCM of 2 and 3 which is 6.

6(-x/2 + y/3) = 6(0)

x + 6y = 16

We then solve the following equivalent system of equations.

-3x + 2y = 0

x + 6y = 16

which gives the solution

**x = 8/5 and y = 12/5**

**For solving the system of equations :**

**(i) + = 0**

**(now for further more steps we need to do addition for that we need to find out the LCM of the denominator)**

**⇒ the LCM of 2 and 3 is "6"**

**(now again we will multiply the equation 1 with 6)**

**⇒ 6×{**

**+ } = {6}0**

**x+6y=16**

**(NOW BY SOLVING THE EQUIVALENT SYSTEM OF EQUATION)**

**with "-3x + 2y = 0" and "x + 6y = 16"**

**By doing the solutions the answers would :**

**⇒ x =**

**⇒ y =**

**∴ x =**

**∴**

**y =**